Pengaruh Literasi Digital Pada Pembelajaran IPS terhadap Kemampuan Berpikir Kritis Siswa Kelas VIII Di SMP Muhammadiyah 22 Kisaran - Nuraini Panjaitan; Rusydi Ananda; Ripho Delzy Perkasa (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This research was conducted to determine the extent to which digital literacy influences social studies learning on the critical thinking skills of class VIII students at SMP Muhammadiyah 22 Kisaran. This research is a quantitative research with data processing in the form of numbers. The data analysis technique used is a simple linear regression test, coefficient of determination test, normality test, linearity test and t-test. Based on the results of the study that obtained a tcount of -1.543 while the ttable value was at a significance level of 5% with N = 30, a ttable of 2.048 was obtained. Then the digital literacy variable has a significance level of 0.134 > 0.05, which means it is not significant. So the value of tcount < ttable is -1.543 <2.048 then Ha is rejected and H0 is accepted, so it can be concluded that there is no effect of digital literacy on social studies learning on the critical thinking skills of class VIII students at SMP Muhammadiyah 22 Kisaran.